Media Literacy in the News Consumption Practices of Young People: An Exploratory Study with Journalism and Communication Students from the University of Coimbra - Lopes Quintino, Cleisyane; Basílio de Simões, Rita (Media & Jornalismo, 2024)
This paper presents the results of a exploratory research study that sought to understand how Journalism and Communication students at the University of Coimbra utilize media literacy competencies in their news consumption. Theoretically, it is based on the conceptualizations of Livingstone (2004) and Hobbs (2010); empirically, it relies on six semi-structured interviews students aged 19 and 20, which were subjected to thematic analysis (Braun & Clarke, 2019; Souza, 2019). The results indicate that although the students possess media literacy competencies, they face multiple challenges in applying these competencies in their daily lives. Participants engage in practices such as daily visits to news websites, following professional channels on social media, training platform algorithms, and cross-referencing information. However, content creation is more compromised, not due to a lack of knowledge but because of fear of negative reception of their opinions in the online environment.